Occurrence of beta-glutamate, a novel osmolyte, in marine methanogenic bacteria. - Robertson, D E (1990)
The unusual compound beta-aminoglutaric acid (beta-glutamate) has been identified by 13C nuclear magnetic resonance spectroscopy in soluble extracts of marine methanogenic bacteria. We examined several methanogen species representing nine genera and found that beta-glutamate occurred in methanococci and two methanogenium strains (Methanogenium cariaci JR1 and "Methanogenium anulus" AN9). The presence of this compound in the methanococci examined was further restricted to thermophilic members of the genus Methanococcus, including Methanococcus thermolithotrophicus strains, Methanococcus jannaschii, and "Methanococcus igneus." The two Methanogenium strains examined were mesophiles. Studies using Methanococcus thermolithotrophicus showed that levels of beta-glutamate in cells of that species were not affected by variation in growth temperature (40 to 65 degrees C), NH4+ (2 to 80 mM), Mg2+ (10 to 50 mM), or K+ (2 to 10 mM) in the medium. In contrast, soluble pools of beta-glutamate and L-alpha-glutamate (the other major free amino acid in all the methanococci) were proportional to NaCl levels in the growth medium. This dependence of beta-glutamate and L-alpha-glutamate concentrations on salt levels in the medium suggests that they function as osmolytes in these cells.